Consumers' demographic factors influencing perceived service quality in e-shopping: some evidence from Nigerian online shopping - Ibrahim, Adamkolo Mohammed; Hassan, Md. Salleh; Pate, Umaru Alhaji (Universiti Putra Malaysia Press, 2018)
The literature has consistently demonstrated that consumers' perception of online stores' service quality is influenced by several factors such as technology use skills, knowledge, income, gender, age, and marital status. This study seeks to determine the differences of perceived service quality (PSQ) in online shopping based on consumers' six demographic factors: age, gender, monthly income (MI), occupation, educational qualification (EQ) and marital status (MS) within four dimensions: access, reliability, ease of use and attentiveness (EoU&A), and Security and Credibility (S&C) adopted from SERVIQUAL scale with modifications. Using snowball method and an online questionnaire, 400 participants comprising students, public servants and private organisations' employees drawn from three Nigerian cities: Abuja, Kano, and Lagos were surveyed. The hypotheses were tested using the scale. Factor analysis yielded the above-mentioned dimensions. Kruskal-Wallis (H test), Mann-Whitney test and Post Hoc test were used to determine the difference of PSQ in online shopping based on the six demographic factors involving each of those dimensions. The results indicate a significant difference of PSQ in age, educational qualification and occupation consistently exists within S&C dimension and variously within the rest of the dimensions. However, no significant difference of PSQ in MI was found in all the four dimensions. Furthermore, gender and MS indicate a significant difference of PSQ within access and EoU&A; only difference based on gender is significant within reliability; while both differences based on gender and MS are not significant within S&C dimension.